Is Job Turnover Countercyclical? - Boeri, Tito (Journal of Labor Economics, 1996)
In recent years several models have been developed in an attempt to explain countercyclical movements of job turnover, the sum of gross job creation and destruction rates. However, only in the United States is a negative and statistically significant correlation between job turnover and employment growth actually observed. In the other countries studied, job turnover is either acyclical or mildly procyclical. Rather than being associated with the greater flexibility of the United States compared with the Western European labor markets, these asymmetries in the cyclical behavior of gross job flows can be attributed to statistical artifacts, namely, with the fact that U.S. job turnover statistics underrepresent the small business sector and with regression to the mean effects.